Implementasi Konsep “Women Oriented” pada Perancangan Interior Fitness Center Khusus Perempuan di Surabaya - Gabriela Cynthia; Ronald Hasudungan Irianto Sitinjak; Linggajaya Suryanata (Intra, 2018)
There are many sports venues for public (unisex) for public in Surbaya. Most women feel do not feel comfortable and free when they are doing exercise with the opposite sex. Besides, women have different sports necessity from men such as the need of lighter load and the preference to exercise in groups. To create a fitness center that can fulfill the sports needs of women whose primary goal is for body performance not for achievement, the sports facilities design are based on the literature and the experts. In addition, designer also do brainstorming to produce a representative fitness center design that focused for women.This women's fitness center becomes a special sports venue because it can fulfill the needs of women's sport optimally and adjust the characteristics of women that can attract women to exercise.With this design, women in Surabaya can exercise comfortably and freely because it is not unisex place so that women can become more healthy, fit and have ideal body.